Utilising social entrepreneurship to facilitate the successful transition of foster youth to adulthood in South Africa - Lesea, Tsakane (Research of GSB, 2018)
Young people, emerging out of the foster care system, often struggle to become productive and self-sustainable adults in society. They are at high risk of being trapped in poverty and unemployment for their entire adult life because they are unable to make a successful transition out of the foster care system to adulthood. The purpose of this study was to explore how social entrepreneurship can be utilised to establish a developmental transitional service to facilitate the successful transition to adulthood of youth in foster care. The research participants were purposefully selected and comprised social workers and foster youths based in the township and the former homelands of the Free State. Data was collected using in-depth interviews and focus groups and was analysed using content analysis. The study found that the current model of the foster care system is not designed to facilitate and support foster youth to make a successful transition to adulthood. This may be ascribed to the following: ● The legislative requirements imposed on this population group, ● The lack of preparatory transition services and ● The limited capacity of social workers to address the needs and challenges of foster youth. The study concludes that intervention is needed in the foster care system to prepare, equip and support foster youth to become productive and self-sustainable citizens. Through the application of the social entrepreneurship framework, this study demonstrates how existing resources and new actors can be leveraged to provide a developmental transitional service that will serve to promote the resilience of youth in foster care and assist them to break the cycle of poverty.